Anaerobic digestion of chicken manure: Influence of trace element supplementation - ÇALLI, BARIŞ (WILEY, 2018)
In this study, anaerobic digestion of nitrogen-rich chicken (egg-laying hen) manure at different trace element (TE) mix doses and different total ammonia nitrogen (TAN) concentrations was investigated in batch digestion experiments. With respect to nonsupplemented TE sets, addition of TE mixture containing 1 mg/L Ni, 1 mg/L Co, 0.2 mg/L Mo, 0.2 mg/L Se, 0.2 mg/L W, and 5 mg/L Fe at TAN concentrations of 3000 mg/L and 4000 mg/L, cumulative CH4 production and CH4 production rate improved by 7-8% and 5-6%, respectively. The results revealed that at a very high TAN concentration of 6000 mg/L, the effect of TE addition was significantly high and the cumulative CH4 production and production rate were increased by 20 and 39.5%, respectively. Therefore, it is concluded that at elevated TAN concentrations the CH4 production that was stimulated by TE supplementation was presumably occurred through syntrophic acetate oxidation.
Keywords: ammonia; anaerobic monodigestion; trace element; syntrophic acetate oxidation; SYNTROPHIC ACETATE OXIDATION; BIOGAS PRODUCTION; METHANE PRODUCTION; LINKING PROCESS; AMMONIA; WASTE; BIOAVAILABILITY; PERFORMANCE; METALS; GROWTH